EMPOWERING STUDENT CRITICAL THINKING SKILLS: HOW GUIDED INQUIRY ENHANCES CRITICAL SKILLS IN ECONOMICS - Radeya Haris Ulul Azmi; Riza Yonisa Kurniawan (Jurnal Eduscience)
Purpose- Critical Thinking is an important skill that students must possess in understanding and applying the concept of Basic Accounting in Economic Subjects. Many students have difficulty analyzing financial transactions and compiling accounting reports. This study aims to analyze students' critical thinking skills in economics subjects of basic accounting materials. The learning process employs a guided inquiry model.